ANALISIS LITERASI NUMERASI DAN BERKARAKTERISTIK HOTS PADA SOAL UJIAN MATEMATIKA KELAS V SD/MI TAHUN PELAJARAN 2020/2021 KECAMATAN MENGANTI GRESIK - Rizka Nur Oktaviani; Cahyani Rahmatika (Jurnal Muassis Pendidikan Dasar, 2022)
The purpose of this study is to describe the results of the numerical literacy analysis, find out the number of characteristics HOTS and calculate the percentage of questions that meet the characteristics HOTS and numerical literacy in SD / MI exam questions for the 2020/2021 school year. This research uses descriptive qualitative research techniques. As well as using data analysis techniques during the field and using the type of content analysis or document. The results showed that of the 3 aspects of the numerical literacy analysis most indikators were obtained in the aspect of making decisions, the coverage of K13 mathematics, and numbers. The highest number of HOTS question characteristics is found in problem solving, analytical, multiplication, contextual problems, and C3 level 2 operational aspects of the verb question. The highest percentage indikators in numerical literacy characteristics is decision making aspect, K13 mathematical coverage, and numeral. The highest percentage of indikators on the characteristics of HOTS, problem solving, analytical thinking, mathematical, scientific and technological utilization, and C3 level 2 KKO.